2001
DOI: 10.1046/j.1432-1327.2001.01998.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel methylated triterpenoids of the gammacerane series from the nitrogen‐fixing bacterium Bradyrhizobium japonicum USDA 110

Abstract: The nitrogen-fixing, symbiotic root-nodule forming bacterium Bradyrhizobium japonicum USDA 110 contained gammacerane derivatives next to triterpenoids of the hopane series. Diploptene, diplopterol, 2 beta-methyldiplopterol, aminobacteriohopanetriol and adenosylhopane were accompanied by tetrahymanol and the corresponding novel methylated homologues 2 beta-methyltetrahymanol, 20 alpha-methyltetrahymanol, and 2 beta,20 alpha-dimethyltetrahymanol. Incorporation of [(2)H(3)]methyl-L-methionine indicated that the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 46 publications
0
55
0
1
Order By: Relevance
“…Bacteria that contain the methylase are found in three different bacterial groups: the acidobacteria, the cyanobacteria, and one major subclade of the rhizobiales within the α-proteobacteria. Of these thirty bacteria, only ten have been tested for hopanoid production and all ten of these strains produce 2-methylhopanoids (17,20,26,27). There are seven Methylobacterium and two Cyanothece strains that have the methylase gene but these specific strains have not been tested for hopanoid production.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria that contain the methylase are found in three different bacterial groups: the acidobacteria, the cyanobacteria, and one major subclade of the rhizobiales within the α-proteobacteria. Of these thirty bacteria, only ten have been tested for hopanoid production and all ten of these strains produce 2-methylhopanoids (17,20,26,27). There are seven Methylobacterium and two Cyanothece strains that have the methylase gene but these specific strains have not been tested for hopanoid production.…”
Section: Resultsmentioning
confidence: 99%
“…It is common for plant symbionts to provide fixed nitrogen to plants or utilize methanol, a byproduct of plant metabolism, as a carbon source (Bravo et al, 2001;Gourion et al, 2006;Meeks, 2009). We found that 74% of hpnP-containing bacteria had either nifD or moxF, which encode proteins necessary for nitrogen fixation and methanol utilization, respectively (Figure 1, middle ring).…”
Section: -Mebhp Production Is Niche Specific Jn Ricci Et Almentioning
confidence: 95%
“…and Nostoc spp. (Figure 1); (Knani et al, 1994;Bravo et al, 2001;Meeks, 2009). To assess whether this observation was non-random, we used the hypergeometric test calculated with the number of plant-associated bacteria estimated at the species level to alleviate bias in the data set.…”
Section: -Mebhp Production Is Niche Specific Jn Ricci Et Almentioning
confidence: 99%
“…Tetrahymanol was first isolated from the ciliate protozoan Tetrahymena pyriformis (Mallory et al, 1963). Besides eukaryotes such as in ferns, fungi, and other ciliates, tetrahymanol was found in addition to hopanoids in the phototrophic purple non-sulfur bacterium Rhodopseudomonas palustris (Kleemann et al, 1990) and in the nitrogen-fixing bacterium Bradyrhizobium japonicum (Bravo et al, 2001). …”
Section: Cyclic Triterpenesmentioning
confidence: 99%